OPTIMALISASI DISTRIBUSI DRIVER MAXIM DI KOTA JAYAPURA MENGGUNAKAN METODE NORTH WEST CORNER (NWC) - Ludovikuss Ngarung; Marto E. Madu, Firminus R. Rhandy, Irwanus Isai, Alfred Dude, Heru Sutejo (CV. ADIBA AISHA AMIRA, 2025)
The online transportation industry, particularly Maxim's online motorcycle taxi service, has become an integral part of the urban transportation system in Jayapura City. This study aims to optimise the distribution of Maxim drivers in three main areas of Jayapura City, namely Abepura, Entrop, and Kota, by applying the North West Corner (NWC) method. The NWC method is used to achieve driver distribution efficiency and minimise operational costs in meeting the transportation needs of the community. Through data analysis and the implementation of the strategies developed, this study demonstrates the potential for improving the operational efficiency of Maxim's services with optimal distribution costs of IDR. 4,250,000.00 per month to serve 200 passengers across the three regions